Building a Genetic Manipulation Tool Box for Orchid Biology: Identification of Constitutive Promoters and Application of CRISPR/Cas9 in the Orchid, Dendrobium officinale - Kui, Ling; Chen, Haitao; Zhang, Weixiong; He, Simei; Xiong, Zijun; Zhang, Yesheng; Yan, Liang; Zhong, Chaofang; He, Fengmei; Chen, Junwen; Zeng, Peng; Zhang, Guanghui; et al. (Frontiers in Plant Science, 2017)
Orchidaceae is the second largest family of flowering plants, which is highly valued for its ornamental purposes and medicinal uses. Dendrobium officinale is a special orchid species that can grow without seed vernalization. Because the whole-genome sequence of D. officinale is publicly available, this species is poised to become a convenient research model for the evolutionary, developmental, and genetic studies of Orchidaceae. Despite these advantages, the methods of genetic manipulation are poorly developed in D. officinale. In this study, based on the previously developed Agrobacterium-mediated gene transformation system, we identified several highly efficient promoters for exogenous gene expression and successfully applied the CRISPR/Cas9 system for editing endogenous genes in the genome of D. officinale. These two basic techniques contribute to the genetic manipulation toolbox of Orchidaceae. The pCambia-1301-35SN vector containing the CaMV 35S promoter and the β-glucuronidase (GUS) and Superfolder green fluorescence protein (SG) as reporter genes were introduced into the plant tissues by the Agrobacterium-mediated transformation system. Fluorescence emission from the transformed plants confirmed the successful transcription and translation of SG genes into functional proteins. We compared the GUS activity under different promoters including four commonly used promoters (MtHP, CVMV, MMV and PCISV) with CaMV 35S promoter and found that MMV, CVMV, and PCISV were as effective as the 35S promoter. Furthermore, we applied the CRISPR/Cas9-mediated genome editing system successfully in D. officinale. By selecting five target genes (C3H, C4H, 4CL, CCR and IRX) in the lignocellulose biosynthesis pathway, we showed that, for a given target, this system can generate edits (insertions, deletions, or substitutions) at a rate of 10% to 100%. These results showed that our two genetic manipulation tools can efficiently express exogenous genes and edit endogenous genes in D. officinale. These efficient research tools will not only help create novel D. officinale varieties, but will also facilitate the molecular genetic investigation of orchid biology.